ANALISIS HUKUM PENYELENGGARAAN PRAKTIK PENGOBATAN TRADISIONAL DI BANDAR LAMPUNG - Rissa Afni Martinouva; Aditia Arief Firmanto (KEADILAN PROGRESIF, 2019)
The implementation of traditional medical practices is supported by several regulationsincluding the Minister of Health Decree No. 1076 / MENKES / SK / VII / 2003 concerningOrganizers of Traditional Medicine and Law No. 36 of 2009 concerning Health. Thisresearch was conducted using the normative-empirical method. The study population wastaken by purposive sampling according to the research objectives. Data analysis in this legalanalysis research uses qualitative methods. The rules and conditions set for the managementof traditional medical practices in Bandar Lampung City are guided by PerMenKes No. 61 of2016 concerning Empirical Traditional Health Services, PP of the Republic of Indonesia No.103 of 2014 concerning Traditional Health Services and Decree of the Head of LampungProvincial Health Office Number 442 regarding Guidelines for Developing TraditionalHealth Services in Lampung Province in 2009. The resulting legal analysis is evident from 60respondents that there are 39 people or 65% already know that the traditional medicinewhere they seek treatment already have a permit, this will increase the confidence of patientsto seek treatment to a legal license. The results of the study of 60 patient respondents wereonly 3 people who were given health insurance by traditional medicine providers. While theremaining 57 patient respondents were not given health insurance by traditional medicineproviders. This proves that only 5% of traditional medicine dares to give health insurance totheir patients. Patients or people who seek treatment are basically entitled to healthinsurance in accordance with the legal basis for health insurance. The Bandar Lampung CityHealth Office has not optimally conducted supervision and education on traditional medicinein the Bandar Lampung City. It is hoped that the mayor's regulations will effectively regulatetraditional medical practices, preventive measures, and make patients more selective inchoosing health healing facilities.